Adaptive Policy for Digital Transformation in Indonesia - Ryan Anggria Pratama; Eki Darmawan (Kemudi, 2023)
The development of digital technology is accelerating and has changed the way people communicate, shop, work and even interact with the government in their daily lives. This is a transformation of the digital era. This study uses the literature review method to analyze articles and case studies related to adaptive policies in digital transformation in Indonesia. In this research, the inhibiting factors and benefits of adaptive policies have been found in digital transformation in Indonesia. The inhibiting factors found include the lack of adequate digital infrastructure, the lack of skilled human resources in the digital field, as well as regulations and policies that have not supported the development of digital technology in Indonesia. However, the benefits of adaptive policies in digital transformation in Indonesia are enormous, including increasing productivity, competitiveness and economic growth. Therefore, it is important for the government to implement adaptive policies in digital transformation in Indonesia in order to minimize the inhibiting factors and maximize the benefits of digital transformation.